Photoacoustic Application for Gas Detection - Hussain, Mohammed A.; Kadhim, Israa Amir (Nahrain University College of Engineering Journal, 2017)
Laser photo acoustic spectroscopy is a technique to detect and measure trace gas using infrared laser radiation. This technology is based on the generation of acoustic wave in a gas excited by a modulated laser beam at a wavelength corresponding to the absorption line of the gas species at the resonance frequency of the acoustic resonator, and detecting this sound wave using a sensitive microphone.This work presents the experimental procedure of laser photoacoustic gas detection at different levels of concentration using Freon-12 as the sample gas.The experimental work has been accomplished by fabricating a photoacoustic cell which consists of an acoustic resonator of 50mm length and 4mm diameter. The resonator is terminated by two gas buffers and partial transmission windows for laser wavelength of 10.6?m. A sensitive microphone has been fixed in midpoint between the mirrors. A CO2 laser of effective power levels 0.7-2W has been used to induce the acoustic wave.The analysis of experimental data has been accomplished using matlab software.